EPCO-16. LACTIC ACID IS AN EPIGENETIC METABOLITE THAT DRIVES GLIOBLASTOMA SURVIVAL AND GROWTH. (9th November 2020) - Torrini, Consuelo; Nguyen, Trang; Shu, Chang; Mela, Angeliki; Humala, Nelson; Mahajan, Aayushi; Karpel-Massler, Georg; Bruce, Jeffrey; Canoll, Peter; Siegelin, Markus
Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor with an unfavorable prognosis and a reprogrammed metabolism. While tumors utilize glucose, there are other carbon sources at their disposal. Originally considered as a waste product of glucose catabolism, lactate accumulates to a significant amount in tumor tissue. We launched our studies with the central hypothesis that lactate is metabolized by GBM cells to promote their survival via modulation of the epigenome. We showed that lactate rescued patient-derived xenograft (PDX) GBM cells from nutrient deprivation mediated cell death and inhibition of growth. Transcriptome analysis, Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq), and CHIP-seq. showed that lactic acid exposure entertained a signature of cell cycle progression, oxidative phosphorylation (OXPHOS) and MYC target expression. LC/MS analysis demonstrated that U-13C-Lactate elicited substantial labeling of TCA-cycle metabolites, acetyl-CoA and histone protein acetyl-residues in PDX derived GBM cells. Given that acetyl-CoA is pivotal for histone acetylation we observed a dose-dependent elevation of histone marks (e.g. H3K27ac), which was rescued by genetic and pharmacological inhibition of lactic acid-uptake, ATP-citrate lyase, p300 histone-acetyl-transferase and OXPHOS, resulting in reversal of lactate mediated protection from cell death or facilitation of GBM growth. CHIP-seq. analysis demonstrated that lactic acid facilitated enhanced binding of H3K27ac to gene promoters and cis-regulatory elements (e.g. super-enhancers). Consistently, ATAC-seq. analysis highlighted enhanced accessibility of the chromatin by lactic acid. Finally, we assessed whether lactic acid is actively metabolized in vivo, utilizing an orthotopic PDX model of GBM. In a combined tracer experiment (U-13C-glucose and 3-C13-lactate), we made the fundamental observation that lactic acid carbons were predominantly labeling the TCA cycle metabolites over glucose, implying a critical role of lactic acid in GBMs and establishing lactic acid metabolism as a novel drug target for GBM that may be targeted with epigenetic drugs.